Incidence of distal ulna fractures in a Swedish county: 74/100, 000 person-years, most of them treated non-operatively. (2nd January 2020) - Moloney, Maria; Farnebo, Simon; Adolfsson, Lars
Abstract : Background and purpose — Fractures of the distal ulna can occur in isolation or in conjunction with a distal radius fracture. They may result in incongruence and instability of the distal radioulnar joint. We investigated the incidence of distal ulna fractures, whether any fracture types were more common, and the methods of treatment used. Patients and methods — Data were collected from patients 18 years or older, treated for a fracture of the distal ulna in Östergötland, Sweden, during 2010–2012. Patients were identified in the patient registry. The fractures were classified according to the AO comprehensive classification of fractures. Results — The incidence of distal ulna fractures was 74/100, 000 person-years. The most common fracture type was that of the ulnar styloid Q1 (79%), followed by the ulnar neck Q2 (11%). Rarest was ulna head fracture, type Q4 (1%). Incidental findings were a mean age of 63 years (SD 18), a concomitant distal radius fracture in 92% of the patients and that 79% were caused by falling from standing height. Internal fixation was performed in 30% of the Q2–Q6 fractures. This indicates that most were considered stable without internal fixation or stable after fixation of a concomitant radius fracture. Interpretation — Our results show that fractures of the distal ulna are not very common, and some fracture types are even rare. There seem to be no consensus on treatment.